Estudo de comutação resistiva em filmes finos de Al2O3 e ZnO para aplicação em dispositivos de “memória resistiva de acesso aleatório” (RRAM) e interruptor eletrônico (IE) - Rodrigues, Aline do Nascimento (2018)
The thin film devices of Pt/Al2O3/Cu/Al2O3/ITO, Pt/ZnO/Cu/ITO, Pt/ZnO/Cu/Phenolite and Pt/ZnO/Cu/Pt films were deposited using a magnetron sputtering system for deposition of the Al2O3, ZnO, Cu and Pt layers. As a top electrode a Pt tip was used and ITO (commercial), Pt and Phenolite (commercial) were used as the bottom electrode. Electrical measurements were forced to verify the existence of Resistive Switching behavior and curves I x V were achieved. For the Pt/ZnO/Cu/ZnO/Pt device deposited at room temperature, no resistive switching was found. A Threshold (non-volatile) switching behavior was found for a Pt/ZnO/Cu/ZnO/Pt sample made with 200 ° C heating during a ZnO film deposition. The Pt/ZnO/Cu/ITO device presented unipolar resistive switching behavior in the negative polarization. The Pt/ZnO/Cu/Phenolite device presented the resistive switching behavior with the formation process. For the device based on Al2O3 the resistive switching was also associated with negative polarization. The filament migration model is suggested to explain the resistive switching behavior in the samples. As retention measures of the devices Pt/ZnO/Cu/ITO and Pt/Al2O3/Cu/Al2O3/ITO The good combination between high and low resistance states over time in non-volatile memory devices.